ANALISIS VEGETASI POHON HUTAN ALAM GUNUNG MANGLAYANG KABUPATEN BANDUNG - Tri Cahyanto; Destiana Chairunnisa; Tony Sudjarwo (JURNAL ISTEK, 2014)
Forest is one of the natural resources on which there is vegetation community dominated by trees and has a very close relationship with the natural world. The purpose of this examination was to examine the composition and structure of natural forest vegetation, including species, stratification and patterns of distribution of natural forest vegetation of Mount Manglayang. In addition to known picture of the distribution of species populations and the influence of environmental factors. The examination was conducted using the method of least squares with purposive sampling, which is done by determining the plot is based on the height above sea level (asl) by 4 plot. Then each plot measuring 10 × 10 m 2 (≥ 10 cm diameter) and subplot size of 5 × 5 m2 (2 ─ rod diameter 9.9 cm). The data obtained for the calculation of the density analysis (K) and relative density (KR), frequency (F) and relative frequency (FR), dominance (D) and relative dominance (DR) and Important Value Index (IVI), in addition to the also calculated species diversity and uniformity. The results indicate there are 11 types of saplings and trees were found. Vegetation sapling that has a value (IVI) a maximum of 70.11% is kind Pinanga coronata. Amounted to 56.21% while the tree is Ficus procera. To dominate the diameter distribution diameter about 2 ─ 60 cm. While the height of the trees that dominate the distribution is in stratum C (4 ─ 20 m). Distribution patterns and tree saplings are regular. Calculation of diversity indices for saplings obtained a value of 1.64 (medium category) and uniformity index value of 0.48 obtained (lower category) and for tree diversity index obtained values of 2.00 (medium category) and obtained a value of the uniformity index 0.53 (lower category).